2016
DOI: 10.1097/aap.0000000000000347
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Captioning for Improving Informed Consent

Abstract: Better methods are needed to improve physicians’ skill in communicating information and to enhance patients’ ability to recall that information. We evaluated a real-time speech-to-text captioning system to aid hearing-impaired patients that simultaneously provided a speech-to-text record for both patient and anesthesiologist. The goals of the study were to assess patient’s recall of an informed consent discussion about regional anesthesia using real-time captioning and to determine whether the physicians found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…With telephone encounters, the only available channel is voice. People who are hearing-impaired are at a disadvantage during in-person and telemedicine encounters but may benefit from the use of sign language interpretation during video encounters or the use of assistive technologies such as real-time captioning during telephone or video encounters ( Spehar et al, 2016 ). People who are visually impaired may rely more heavily on auditory and kinesthetic channels during in-person encounters, which could pose particular challenges for clear communication during either telephone or two-way video encounters.…”
Section: Clear Communication Best Practicesmentioning
confidence: 99%
“…With telephone encounters, the only available channel is voice. People who are hearing-impaired are at a disadvantage during in-person and telemedicine encounters but may benefit from the use of sign language interpretation during video encounters or the use of assistive technologies such as real-time captioning during telephone or video encounters ( Spehar et al, 2016 ). People who are visually impaired may rely more heavily on auditory and kinesthetic channels during in-person encounters, which could pose particular challenges for clear communication during either telephone or two-way video encounters.…”
Section: Clear Communication Best Practicesmentioning
confidence: 99%
“…Information retained by patients during informed consent for elective surgery varies and agreement on the use of information sheets is discussed without a definite conclusion based on evidence-based research 42–44 . Information supplied to a patient may be understood, but it can be easily and quickly forgotten.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is unclear if the caption benefit is fleeting or extends into long-term speech memory. Finally, there is some evidence to suggest that real-time text captioning may provide benefits in real-world scenarios, such as for improving informed consent; Spehar et al (2016) showed that patients retained more information during simulated informed consent when consent was done with real-time assistive text captioning.…”
Section: Introductionmentioning
confidence: 99%